Pendidikan karakter islami untuk siswa SMP/MTs / Ibnu Burdah; Editor, Andriansyah Syihabuddin dan Andhika Prasetya Kusharsanto - IBNU Burdah; ANDRIANSYAH Syihabuddin; ANDHIKA Praseya Kusharsanto (Erlangga, 2013)
84 hlm. ; 21 cm.